PERCEPTION AND ATTITUDE OF PHYSIOTHERAPIST TOWARDS ARTIFICIAL INTELLIGENCE IN HEALTHCARE AND REHABILITATION: A SURVEY - Isha,; Sonam Jain,; Syed Hamad Raza,; Yashfa Parveen,; Dr. Muskan Jain (PT),; Dr. Mimoh Agrawal (PT),; Dr. Radhika Dixit (PT),; Dr. Ranjit Tiwari (PT), (The Bioscan, 2025)
The rapid integration of Artificial Intelligence (AI) into healthcare has given rise to questions about its acceptance and implementation in various domains, including physiotherapy. The aim of this research was to evaluate physiotherapists' knowledge, attitudes, and perceptions of AI use in healthcare and rehabilitation. A cross-sectional survey of 353 Indian physiotherapists was administered via a structured questionnaire sent through Google Forms. The questionnaire explored demographics, awareness of AI, actual use, training provided, and perceptions of benefits, applications, and future role of AI in physiotherapy. Results indicated that while 97% of respondents reported having heard of AI in general, awareness dropped to 77% when it was referred to in the context of rehabilitation. Less than 38% of the respondents had formal training in AI. Overall perception of AI was moderately positive in nature but large gaps were observed between awareness and actual application in clinical practice. Statistical analysis showed a significant relationship between employment sector and concerns or opinions about AI. Gender differences were observed in perceived benefits but not in use or impact. A moderate positive correlation was observed between perceived applications and benefits of AI. The study documents a high awareness but low hands-on experience and training among physiotherapists, reflecting a clear knowledge-to-practice gap. These findings emphasize the urgent need for structured AI education and training in physiotherapy curriculum and continuing education. As healthcare evolves with AI, it is essential to know the readiness and concerns of physiotherapy professionals to facilitate ethical and effective application in clinical practice.